2016
DOI: 10.1080/13813455.2016.1195411
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the LDL-C/apoB ratio in the overall evaluation of atherogenicity of lipid profile

Abstract: Low levels of apoE are most likely a cause of reduced clearance of TG-rich lipoproteins, which promotes the formation of sd-LDL. Determination of the LDL-C/apoB ratio can be used for monitoring qualitative changes in lipid profile, in addition to traditional lipid variables indicating quantitative changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…An LDL-C/apoB ratio of 1.2 has been suggested to correspond to an LDL diameter of 25.5 nm, which is the cut-off value for distinguishing LDL pattern A (large buoyant LDL) from LDL pattern B [small dense (sd)-LDL] [ 7 , 8 ], indicating the presence of a large quantity of sd-LDL. In fact, the Québec Cardiovascular Study demonstrated that in patients with LDL-particle sizes of 25.5 nm or smaller, the CAD incidence increased significantly as the serum LDL-C level increased, while in patients having large LDL-particle sizes of 26.0 nm or greater, no significant difference in CAD events was observed according to the absolute serum LDL-C level [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An LDL-C/apoB ratio of 1.2 has been suggested to correspond to an LDL diameter of 25.5 nm, which is the cut-off value for distinguishing LDL pattern A (large buoyant LDL) from LDL pattern B [small dense (sd)-LDL] [ 7 , 8 ], indicating the presence of a large quantity of sd-LDL. In fact, the Québec Cardiovascular Study demonstrated that in patients with LDL-particle sizes of 25.5 nm or smaller, the CAD incidence increased significantly as the serum LDL-C level increased, while in patients having large LDL-particle sizes of 26.0 nm or greater, no significant difference in CAD events was observed according to the absolute serum LDL-C level [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An LDL-C/ApoB ratio lower than 1.2 may be used for distinguishing large buoyant LDL from small dense LDL. The incidence of CHD increases significantly in patients with small LDL-particle sizes[11, 12, 24, 25]. In the current cohort study, the results of the logistic regression analysis revealed that low LDL-C/Apo B ratio is an independent predictor of CHD.…”
Section: Discussionmentioning
confidence: 66%
“…sd‐LDL ELISAs are currently still expensive and their elaborate process makes them impractical for implementation within clinical routine; ApoB is a more feasible test to perform within a clinical setting. Studies suggest that the ApoB to LDL ratio may be a useful tool for assessing the overall atherogenicity of a lipid profile . Some interventional methods to explore in future studies include differing diets, physical activity, antioxidant supplementation with Omega‐3, and the administration of statins.…”
Section: Should We Therefore Favor a Tacrolimus‐ And Mmf‐based Immunomentioning
confidence: 99%